Da'wah and Interpersonal Attraction of Popular Figures in Indonesian Television - Muhammad Firousyurahman (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2018)
Perfection and success in preaching depends on the behavior, actions, and ways of presenting the material. In preaching, da’i is required to have the ability and creativity that will impress the audience with his message. The research on the preaching of the attractions of Ustad IL and AL has a purpose to find out the unique ways and art of preaching so that preaching messages can be accepted by the community and preparations before preaching. In line with the objectives, this study uses qualitative methods with a case study approach. In preaching, Ustad IL and AL have special art in displaying their attractions on the stage. Besides having physical attraction, they also have strength in language style, sound style, gesture, dress style and that can all influence, and make an interest in the audience.